2018
DOI: 10.2965/jwet.17-020
|View full text |Cite
|
Sign up to set email alerts
|

Polarity-Molecular Weight Profile of Extracellular Polymeric Substances in a Membrane Bioreactor: Comparison between Bulk Sludge and Cake Layers

Abstract: Extracellular polymeric substances (EPS) are reported to be the major foulant in membrane bioreactor (MBR) processes. It is important to understand the EPS fractions which cause irreversible fouling to reduce operation cost and energy consumption in MBR. In this study, we developed polarity-molecular weight profiling, in which EPS components were plotted on two-dimensional matrix of its polarity and molecular weight, and applied it to investigate EPS of bulk sludge and cake layers from a labscale MBR. The EPS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…It is known that loosely bound EPS has strong affinity toward membrane fouling, especially substances larger than 100 kDa such as polysaccharides which will accumulate on the membrane surfaces to form cake layer (Hong et al, 2018). In MD process, the LMW polysaccharide could cause immediate and irreversible plugging and narrowing of membrane.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that loosely bound EPS has strong affinity toward membrane fouling, especially substances larger than 100 kDa such as polysaccharides which will accumulate on the membrane surfaces to form cake layer (Hong et al, 2018). In MD process, the LMW polysaccharide could cause immediate and irreversible plugging and narrowing of membrane.…”
Section: Resultsmentioning
confidence: 99%
“…HMW sEPS that was deposited onto the virgin membranes would also have the chance to be further degraded into smaller molecules due to consistent high temperature imposed in the MD application. These broken-down fractions can be pulled into the conditioned micropores to plug the flow channels, eventually leading to mass production of 450 kDa to 1100 kDa smaller chain polysaccharides from either living or dead cells (Hong et al, 2018). Thus, in MD process, monosaccharides and LMW components that are majorly contained in the sEPS would cause immediate and irreversible plugging and narrowing of membrane.…”
Section: Molecular Weight Distribution Of Polysaccharidementioning
confidence: 99%
“…Meanwhile, their study postulated that the characteristics of AOM should not be overlooked though the dissolved organic carbon is always considered as a decisive factor of biofouling potential in addition to operating conditions and membrane properties (Henderson et al, 2008). Moreover, hydrophobic substances from the sEPS could be adsorbed by the substrate via pore conditioning, facilitating the accumulation of hydrophilic loosely bEPS on these type of conditioned ‘pockets’ and promoting biofilm formation (Hong et al, 2018). It was always reported that algal culture was highly hydrophilic with the presence of polysaccharides and hydroxyl acids (Rafiee et al, 2020).…”
Section: Extracellular Polymeric Substances Quantification Techniquesmentioning
confidence: 99%
“…methyl-, ethyl-), hydrophobic amine and benzyl-groups. (Flemming and Wingender, 2010;Hong et al, 2018;Neu, 1996;Sutherland, 2001) Some EPS exhibit hydrophilic and hydrophobic regions (e.g. emulsan, a highly acetylated polysaccharide, allowing detachment from hydrophobic surfaces) or hydrophobic moieties (e.g.…”
Section: Heterogeneous Molecular Characteristics Confer Stickiness To...mentioning
confidence: 99%